Cartas de Caldas [Francisco José] ilustradas. Bogotá, Universidad Distrital Francisco José de Caldas/Casa Museo Caldas/ Academia Colombiana de Ciencias Exactas, Físicas y Naturales, 2016, 548p. (2017)
Nuevo Reino de Granada